Studi LCPUFA dan variant genetik enzim Fatty Acid Desaturase pada masa kehamilan di Asia masih langka (Lembaga Penerbitan Unversitas Esa Unggul, 2023)
Enourmos body of literatures reported that inadequacy of LCPUFAS (long chain polyunsaturated fatty acids) during pregnancy is associated with premature birth and newborn low birth weight. LCPUFAs may modified pregnancy outcome by modulating blood fatty acid, lipid profile and apo-lipoprotein. Current study reviewed literatures that investigate the association between maternal LCPUFAS and genetic variant of FADS (fatty acid desaturares), which act on endogenous synthesis of omega 3 precursors, and birth outcome in Asian countries particularly Indonesia. Using accessed PUBMED and Google Scholar database during January 2015 to December 2022 with a query of LCPUFAs, FADS, pregnancy and birth outcome, there were nine peer-reviewed literatures in English and two local literatures. Current finding confirmed the scarcity of literatures that associating LCPUFAS, FADS during pregnancy and birth outcome in Asian countries particularly in Indonesia. The finding also highlighted the role of LCPUFAS in prolonged gestation and desirable birth outcome. Genetic variant of FADS was indicated to modify the association of maternal LCPUFAs and birth ouctome. The scarcity of literaturs encourages other researcher to conduct further investigatation on this topic